Challenges and Opportunities in Education Financing in the Era of Digital Transformation - Banny Haruna; Custanti Custanti; Sutrisno Sutrisno (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Digital transformation has significantly changed the education system, including in the aspect of financing, which is a key factor in improving the quality of and access to education. This study aims to analyze the challenges and opportunities of education financing in the era of digital transformation and to formulate an adaptive and sustainable conceptual model. The method used is a descriptive qualitative approach through a literature review, analyzing various scientific literature, policy reports, and related research findings from the past 5–10 years. The research findings indicate that the main challenges include the digital divide, limited education budgets, low digital literacy, and the complexity of digital system-based governance. On the other hand, digital transformation opens opportunities through the utilization of financial technology (fintech), digital platforms, and big data, which can enhance financial inclusion, budget efficiency, and transparency in the management of education funds. A synthesis of the findings indicates that digital transformation serves as a strategic mediator capable of converting challenges into opportunities through technological innovation and multi-stakeholder collaboration. Therefore, an integrative approach is required that combines adaptive policies, human resource capacity building, and the optimization of digital technology to create an inclusive, efficient, and sustainable education financing system in the digital era.